Prevalence and Pattern of Inhalant Allergens among Allergic Rhinitis Patients in Vellore – A Cross Sectional Study - krithiga Sivakumar; Sivakumar Ethirajan; Sivachandrabose k (Bengal Journal of Otolaryngology and Head Neck Surgery, 2023)
INTRODUCTION: Allergic rhinitis is a global health problem but often neglected and its burden, underestimated. Knowledge on its epidemiology is important for its diagnosis and treatment. Hence, this study was conducted to assess the prevalence and pattern of various inhalant allergens among allergic rhinitis patients in Vellore district.